2017
DOI: 10.1007/s13311-017-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Exerts only Temporary Antiepileptogenic Effects but Longer-Lasting Positive Effects on Behavior in the WAG/Rij Rat Absence Epilepsy Model

Abstract: One of the major challenges in the epilepsy field is identifying disease-modifying drugs in order to prevent or delay spontaneous recurrent seizure onset or to cure already established epilepsy. It has been recently reported that fingolimod, currently approved for the treatment of relapsing-remitting multiple sclerosis, has demonstrated antiepileptogenic effects in two different preclinical models of acquired epilepsy. However, to date, no data exist regarding the role of fingolimod against genetic epilepsy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 86 publications
1
37
0
Order By: Relevance
“…However, these effects were transient and faded 5 months after drug washout. The drug showed a longer‐lasting (up to 6 months) improvement of cognitive decline in this model . Finally, fingolimod reduced by half the 2.5‐fold increase in seizure‐induced P‐glycoprotein expression measured 2 days after Li + pilo‐SE in the rat hippocampus (1 mg/kg ip at the time of SE induction, then daily for 2 days).…”
Section: Fingolimodmentioning
confidence: 75%
See 1 more Smart Citation
“…However, these effects were transient and faded 5 months after drug washout. The drug showed a longer‐lasting (up to 6 months) improvement of cognitive decline in this model . Finally, fingolimod reduced by half the 2.5‐fold increase in seizure‐induced P‐glycoprotein expression measured 2 days after Li + pilo‐SE in the rat hippocampus (1 mg/kg ip at the time of SE induction, then daily for 2 days).…”
Section: Fingolimodmentioning
confidence: 75%
“…The drug showed a longer-lasting (up to 6 months) improvement of cognitive decline in this model. 263 Finally, fingolimod reduced by half the 2.5-fold increase in seizure-induced P-glycoprotein expression measured 2 days after Li + pilo-SE in the rat hippocampus (1 mg/kg ip at the time of SE induction, then daily for 2 days). This effect was associated with prevention of the threefold increase in hippocampal COX-2 and TNF and resulted in a twofold increased brain delivery of phenytoin, suggesting a potential value of fingolimod as adjuvant therapy for drug resistance to some ASDs.…”
Section: Fingolimodmentioning
confidence: 93%
“…Indeed, our previous data clearly showed that butyrate modulates innate immunity and oxidative stress, suppressing toll-like receptor and nuclear factor-kB activation in liver. [74][75][76][77] In conclusion, we provide evidence of the efficacy of butyrate and its potential utility in the prevention of VPAinduced liver injury. The study of functional data on seizures and animal behavior, and mechanism of actions of VPA and NaB, as HDAC inhibitors, are a part of a project financed by the Italian Ministry of Research (MIUR; prot.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the number of rats used, all experimental groups were subjected to several tests. When the same animal was subjected to several tests, at least one day (range one to three days) was allowed for recovering, as previously reported [25]. All behavioral tests were carried out under controlled environmental conditions, such as temperature, humidity, and light intensity (dim illumination), and all tests, except for passive avoidance, were performed with the support of video-tracking software (EthoVision XT8; Noldus Technology, Wageningen, the Netherlands).…”
Section: Behavioral Testsmentioning
confidence: 99%
“…No foot shock was delivered in this trial. Retention memory is directly linked to the latency to enter into the dark compartment: The better the memory, the greater the latency [25,27].…”
Section: Passive Avoidance (Pa)mentioning
confidence: 99%